2011
DOI: 10.4297/najms.2011.375
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in a rural community of Nigeria

Abstract: Aim:To determine the prevalence of urinary tract infection (UTI) in Okada, a rural community in Nigeria, and the effect of age and gender on its prevalence as well as the etiologic agents and the susceptibility profile of the bacterial agents.Patients and Method:Clean-catch midstream urine was collected from 514 patients (49 males and 465 females). The urine samples were processed and microbial isolates identified. Susceptibility testing was performed on all bacterial isolates.Result:The prevalence of urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
63
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 7 publications
30
63
6
1
Order By: Relevance
“…From total 830 urine samples collected from CA-UTI patients 292 (35.1%) yielded significant pathogens. A similar value of 39.7% was obtained by Oladeinde et al in rural community from Nigeria [13]. The culture positive rate for CA-UTI was higher in our study in comparison with studies reported from Aligarh, India (10.86%) [5].…”
Section: Resultssupporting
confidence: 89%
“…From total 830 urine samples collected from CA-UTI patients 292 (35.1%) yielded significant pathogens. A similar value of 39.7% was obtained by Oladeinde et al in rural community from Nigeria [13]. The culture positive rate for CA-UTI was higher in our study in comparison with studies reported from Aligarh, India (10.86%) [5].…”
Section: Resultssupporting
confidence: 89%
“…The results may not reflect the true prevalence as most patients are treated empirically for Urinary Tract Infection (UTIs). This study indicated that UTI is more common in female (74%) than males (26%) that is similar with previous study in 2017, India with 73.97% in females and 26.02%) UTI prevalence to males (Lawhale & Naikwade, 2017) and other studies (Dash, Padhi, Mohanty, Panda, & Parida, 2013;Oladeinde, Omoregie, Olley, & Anunibe, 2011;Shah, Wasim, & Abdullah, 2015). Possible reasons for common UTI in females including short urethra, close proximity of vagina with urethral meatus, rich microbial flora with rectal mucosa and sexual intercourse have been reported (Oladeinde et al, 2011;Shah et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This does not agree with the findings of [1] who found a higher UTI prevalence in males (58.3%) than in the female outpatients (41.7%). The reason for this was not clear as it contradicts reports of studies on UTI by the following authors [38] [42] [44] [46]- [50].…”
Section: Discussionmentioning
confidence: 58%